The equilibrium and kinetic modelling of the biosorption of copper(II) ions on Cladophora crispata - Özer, A; Özer, D; Ekiz, HI (Springer, 2004)
The biosorption of Cu(II) ions on Cladophora crispata was investigated as a function of the initial pH, temperature and initial Cu(II) ion concentration. Algal biomass exhibited the highest Cu(II) uptake capacity at 25degreesC and at the initial pH of 4.5. Equilibrium data fitted very well to both the Langmuir and Freundlich isotherm models. The pseudo second order kinetic model was applied to describe the kinetic data and the rate constants were evaluated in the studied concentration range of Cu(II) ions at all the temperatures studied. The experimental data fitted well to the pseudo second order kinetic model with a high correlation coefficient (R-2 > 0.99), which indicates that the external mass transfer limitations in the system can be neglected and the chemical sorption is the rate-limiting step. The pseudo second order kinetic constants were also used to calculate the activation energy of Cu(II) biosorption.
Keywords: adsorption equilibrium; pseudo second order kinetics; activation energy